The Epistemology of Knowledge in Classical Sufism; A Study of Al-Muḥāsibī’s Thought (781 AD- 857 AD) - Miftahul Ula (Millati: Journal of Islamic Studies and Humanities, 2025)
Al-Washaya, Risalah al-Mustarsyidin and the book al-’Aql wa Fahmu al-Qur’an. The research data were analyzed by content analysis and hermeneutic philosophy analysis. The results showed that the source of knowledge of Sufism according to al-Muhasibi is revelation materialized in the Qur’an and hadith and reason. Reason serves for confirmation (tatsabut) for various problems. Reason is an indicator of one’s devotion which is obtained after performing the typical stages of a Sufi, namely by purifying the heart from various diseases and impurities and carrying out obedience to God and doing good to other creatures. It was this that led al-Muhasibi to believe that it was the knowledge of Sufism that had the most convincing validity.